PEMANFAATAN VIDEO ANIMASI INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Alya Nabila; Muhammad Surya Abdi; Nindia Zahwa Prishananda; Raudah; Ahmad Suriansyah; Wahdah Refia Rafianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Rapid technological advances are driving the world of education, particularly at the elementary school level, to reform the learning process. In reality, teaching and learning activities often rely on conventional approaches that tend to make students less active, resulting in low motivation and understanding of the material. This study aims to examine the use of interactive animated video media as a learning tool that can improve the motivation and learning outcomes of elementary school students. The method used is a literature study by reviewing various scientific sources, such as journal articles, reference books, and research reports relevant to the research topic. The collected data were analyzed descriptively qualitatively through the stages of sorting information, grouping data, and drawing comprehensive conclusions. The results show that the application of interactive animated video can create a more interesting and enjoyable learning atmosphere, increase student learning interest, and help them understand learning concepts more clearly. In addition, this media is considered effective in presenting abstract material in a more concrete way and is able to accommodate differences in student learning styles, thus contributing positively to improving the quality of learning in elementary schools.